TAXING ONLINE GAMBLING IN INDONESIA: A LEGAL PERSPECTIVE ON ITS REALIZATION AND FUNCTIONS - Pratama, Zharezky Yoga; Rizaldi , Narandra Adhika (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
Indonesia has a longstanding and contentious history of debates surrounding the taxation of online gambling. The purpose of this research is to examine the feasibility of implementing a tax on online gambling in Indonesia, despite its legal prohibition. The study addresses concerns over whether such taxation implies legalization, a contentious issue in a predominantly Muslim country that opposes gambling for moral and religious reasons. The methodology used is normative legal research, using a conceptual, comparative, and statutory approach. This study reviews Indonesian tax functions and compares them with foreign practices, such as the United States, which successfully taxes illegal incomes without legalizing the underlying activities. The findings suggest that taxing online gambling could fulfill two significant functions of taxation: regulerend and budgetary. The regulerend function discourages the participation of online gambling, while the budgetary function generates revenue for the state. This approach would not equate to legalization but rather leverage Indonesia’s income tax laws. Countries like the United States demonstrate that taxing illegal income can reduce incentives for criminal behavior by imposing financial obligations. Adopting a similar approach in Indonesia, with clear punitive measures for tax evasion on illegal income, has the potential to curb gambling practices and increase state revenue.